2006
DOI: 10.1128/mcb.02324-05
|View full text |Cite
|
Sign up to set email alerts
|

Expression of rRNA Genes and Nucleolus Formation at Ectopic Chromosomal Sites in the Yeast Saccharomyces cerevisiae

Abstract: We constructed yeast strains in which rRNA gene repeats are integrated at ectopic sites in the presence or absence of the native nucleolus. At all three ectopic sites analyzed, near centromere CEN5, near the telomere of chromosome VI-R, and in middle of chromosome V-R (mid-V-R), a functional nucleolus was formed, and no difference in the expression of rRNA genes was observed. When two ribosomal DNA (rDNA) arrays are present, one native and the other ectopic, there is codominance in polymerase I (Pol I) transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…In some instances this is achieved by amplification of specific loci. rDNA amplification occurs in amphibian oocytes, the macronucleus of Tetrahymena and budding yeast (Brown and Dawid, 1968; Claycomb and Orr-Weaver, 2005; Gall, 1968; Kobayashi et al, 1998; Nordman and Orr-Weaver, 2012; Oakes et al, 2006; Pesin and Orr-Weaver, 2008; Yao et al, 1974) and thus appears to be a common mechanism used to accommodate different protein synthesis needs in different tissues and under changing environmental conditions. While rDNA amplification is not uncommon, amplification of selective genes is rarely used to up-regulate gene expression and in the instances where this has been described, occurs in cells destined to die.…”
Section: Gene Copy Number Alterations As a Source Of Adaptive Potentimentioning
confidence: 99%
“…In some instances this is achieved by amplification of specific loci. rDNA amplification occurs in amphibian oocytes, the macronucleus of Tetrahymena and budding yeast (Brown and Dawid, 1968; Claycomb and Orr-Weaver, 2005; Gall, 1968; Kobayashi et al, 1998; Nordman and Orr-Weaver, 2012; Oakes et al, 2006; Pesin and Orr-Weaver, 2008; Yao et al, 1974) and thus appears to be a common mechanism used to accommodate different protein synthesis needs in different tissues and under changing environmental conditions. While rDNA amplification is not uncommon, amplification of selective genes is rarely used to up-regulate gene expression and in the instances where this has been described, occurs in cells destined to die.…”
Section: Gene Copy Number Alterations As a Source Of Adaptive Potentimentioning
confidence: 99%
“…While the rDNA to be transcribed exists as repeats in eukaryotic NORs, Karpen et al demonstrated that insertion of only one rRNA gene in the polytene chromosomes of Drosophila melanogaster caused the formation of “mini-nucleoli” which produce pre-rRNA and recruit a nucleolar antigen (Karpen et al 1988). It should be noted, however, that the amplification process of polytenization may have increased the number of juxtaposed rRNA genes, enhancing Pol I recruitment and pre-rRNA production (Oakes et al 2006). Therefore, the results from Karpen et al raised questions regarding whether a single rDNA repeat in somatic mammalian cells is sufficient to induce nucleolar formation.…”
Section: Requirements For Nucleolar Assembly and Functionmentioning
confidence: 99%
“…Nucleolar structure is also disrupted when yeast are forced to transcribe the chromosomal rDNA repeats with RNAP II, rather than RNAP I (48). The entire yeast rDNA array can be shifted to another location within the genome, but in this case only minor phenotypic changes are observed, despite the nucleolus changing its position in the nucleus (49). This is consistent with a limited amount of published data that shows that specific rDNA:non rDNA interactions are sequence specific and independent of the chromosomal position of the non-rDNA locus (42).…”
Section: The Nucleolus As An Organizer Of Genome Structurementioning
confidence: 99%